Assessment of actuator disc models in predicting radial flow and wake expansion. Issue 207 (December 2020) - Micallef, Daniel; Ferreira, Carlos; Herráez, Iván; Höning, Leo; Yu, Wei; Capdevila, Hugo
Abstract: Navier-Stokes actuator disc models have become a mature methodology for investigating wind turbine rotor performance with numerous articles published annually making use of this approach. Despite their popularity, their ability to predict near wake expansion remains questionable. The objective of this paper is to analyse the predictive ability of actuator disc models and compare results with other popular types of codes. The methodology employs the use of an actuator disc Computational Fluid Dynamics approach to model an actuator disc and a real (finite bladed) turbine case. Results are validated with existing experimental data. In addition, results from an actuator line model with and without tip corrections and a 3D vortex panel method are presented to aid the discussion. Results show that all models give a poor wake expansion prediction particularly in the inboard to mid-board areas. A good prediction is found in the outboard regions. In addition, contrary to the well known positive effects of tip corrections on load prediction, this work shows that this does not bring any particular benefit on wake expansion prediction. The conclusions from this work help to guide the use of actuator disc models in more complex flow scenarios including floating offshore wind turbine analysis. Highlights: Actuator disc approaches show good prediction of wake expansion in the outboard areas of the rotor. Poor wake expansion prediction was observed over the inboard and mid-board regions using the actuator disc approach. Dimensionless axial multiplied by radial induction factors in the near wake region is not sensitive to the thrust coefficient.